Being biblical in a pluralistic academy - Vanhoozer, Kevin J. (Andrews University Seminary studies, 2019)
This essay examines two senses of what it means to be biblical in a pluralistic academy. The first is to examine the Bible as a document of the university, susceptible to many kinds of critical probing. The rest of the essay explores the second way, which is to use the Bible as the authoritative control story that articulates how Christians view Jesus Christ as the ground, grammar, and goal of both the university and the universe itself. I examine how biblical authority should and should not be deployed in the academy by looking at the natural and human sciences. I then draw out four implications for the importance of using the Bible as the social imaginary of academic research, with special emphasis on how being biblical avoids the cardinal sin of academicians: reductionism.